Phytochemical assisted synthesis of size and shape tunable gold nanoparticles and assessment of their catalytic activities. Issue 55 (18th May 2016) - Phukan, Shreemoyee; Bharali, Pankaj; Das, Arup K.; Rashid, Md. Harunar
Abstract : A faster and environmentally viable phytochemical assisted reduction method of synthesizing catalytically active gold nanoparticles (GNPs) is reported. Abstract : A faster and environmentally viable phytochemical assisted reduction method of synthesizing gold nanoparticles (GNPs) is reported. Leaf extract of Amentotaxus assamica plant is used for the first time both as reducing and capping agent for GNPs. The size and shape of GNPs can be systematically tuned by varying the concentrations of metal ion and extract. The GNPs are characterized by microscopic, spectroscopic and diffractometric techniques. The microscopic results confirmed that when the concentration of HAuCl4 is increased, keeping the concentration of the plant extract fixed, the size increase is accompanied by formation of polygonal GNPs. However, when the concentration of plant extract is decreased, keeping the concentration of HAuCl4 the same, the population as well as the size of polygonal GNPs are increased. The results are further confirmed from UV-vis spectroscopic analysis in which all the samples show a major absorption peak at 537 nm, which is accompanied by another weak peak in the higher wavelength region as the polygonal GNPs are formed at higher HAuCl4 concentration. This longitudinal band red-shifted as the size of polygonal GNPs increased. X-ray diffraction studies suggest the formation of pure crystalline GNPs. These GNPs show excellent catalytic activity towards borohydride reduction of different isomeric nitrophenols.